Newspaper cutting : The Lancet : The Situation in Spain
016a-0030-001 THE SITUATION IN SPAIN MUCH is said nowadays about the way in which rapid communications have diminished distances. Yet the civil war in Spain is still so far away as to be barely credible. The feeling that these events are only newspaper stories must be the chief explanation of our comparative failure to respond to the desperate needs of people living only a few days' sail to southward of us. In the past week or two something has been done to bring home the realities of the situation in the Basque provinces. Serious attempts are being made to remove from Bilbao women and children whose danger is evident from the fate of Guernica, and we understand that money for this purpose will be gratefully received by the National Joint Committee for Spanish Relief, 35 Marsham-street, London, S.W.1. Associated with the committee in its general work in Spain are the Save the Children Fund (20, Gordon-square, W.C.1) and the Friends' Service Council (Friends House, Euston-road, N.W.1), both of which, despite deficient funds, are doing much to dispel the idea that the English have ceased to care. An illustrated pamphlet called "Children in Spain Today" reaches us from the Committee Against Malnutrition, with a foreword signed, among others, by Dame Janet Campbell, Miss Harriette Chick, and Miss Edith Pye. It shows that already in January the number of refugees in the Government area exceeded a million, or 10 per cent. of the population, and it adds that "the public conscience in western countries may have to prepare itself for a great relief effort in the near future, if the misery of a famine upon our European continent however short its duration and restricted its scope is not to be repeated in our time.'' There is no collapse of health and welfare services, however, on the Government side of the lines; indeed they have expanded remarkably. Hence whatever help is given for the prevention or relief of distress is likely to be used effectively. Finally - which directly concerns the medical profession and its allies - there is a constant demand for medical and surgical equipment and supplies. The goodwill of manufacturers is now being asked for a scheme by which workpeople engaged in making such things may work overtime and thus earn credit with their employers for organisations sending aid to Spain. It is believed that a large proportion of employees would gladly give a few hours a week to such voluntary work, and since the firms concerned would secure the orders for equipment they would gain rather than lose by according the facilities asked for. We hope that many firms may be willing to give the scheme sympathetic consideration. It is planned by Voluntary Industrial Aid for Spain (32, Great Ormond-street, W.C.1), which is already applying the principle to the manufacture of motor-cycle sidecar ambulances. These have proved their worth in mountainous regions where other vehicles cannot reach the wounded. The Lancet May 8 1937 292/946/16a/32(i)